Geomorphological evolution and sediment dispersal processes in strike-slip and extensional composite basins: A case study in the Liaodong Bay Depression, Bohai Bay Basin, China. (December 2019) - Liu, Lei; Chen, Hongde; Wang, Jun; Zhong, Yijiang; Du, Xiaofeng; Gan, Xia; Zou, Hao
Abstract: The geomorphological evolution and sediment dispersal processes of the Liaodong Bay Depression (LBD), a strike-slip and extensional composite basin in the Dongying Formation, were studied using 3D seismic, drilling, and logging data in an attempt to understand the diversity of sand-controlling factors and the complexity of the sand dispersal processes. The LBD was mainly supplied by sediments from the eastern side, which originated in the Yanshan Fold system (comprising the Dashi River, Liugu River, and Lin River systems) and sediments from the western side, which originated from the Jiaoliao Uplift system (comprising the Daqing River and Fuzhou River systems). Different sediment provenances had various sediment supply capacities depending on the composition of the source rocks. Sediments were injected into the basin through the channels identified from two interpreted southwest-to northwest-orientated seismic sections. Strata of the Dongying Formation could be divided into three sequences, and comprised shallow-deep lacustrine deposits, braided river delta deposits, fan delta deposits, and sublacustrine fan deposits. Based on the established sequence stratigraphic framework, the strata thickness distribution and sequence of geomorphological evolution could be restored from 3D seismic data of the LBD. By analyzing the distribution and migration of depocenters and the distribution of channels, sediment pathways in the basin could be determined under high flux sediment supply. In terms of five interpreted seismic sections from north to south, we demonstrated that in addition to immense changes in tectonic depositional style in the eastern areas of the basin, the sediment dispersal processes in different areas exhibited prominent discrepancies in sediment accumulations from diverse depositional systems. Tectonic activities, efficient sediment provenance, distribution of channels, and sequence geomorphology jointly controlled the sediment dispersal processes in the deposition areas and determined the potential reservoir distribution. Highlights: Geomorphological evolution and sediment dispersal of a bay depression was studied. Strata thickness and sequence-geomorphology was restored from 3D seismic data. Distribution of incised valleys and sediment pathways in the basin were determined.